Real-time wave excitation force estimation for an experimental multi-DOF WEC. (1st October 2020) - Hillis, A.J.; Brask, A.; Whitlam, C.
Abstract: A wave energy converter (WEC) needs an active control strategy to maximise efficiency in a wide range of operating conditions. Many control strategies require knowledge of the wave excitation force, a quantity which cannot be measured in operation. In this study, two methods based upon Kalman filters are tested with an experimental 1:25th scale multiple degree-of-freedom WEC. A stochastic and a periodic Kalman estimator are implemented, using only quantities which are measurable in practice. Methods for tuning the estimators are discussed, and sensitivity to nonlinearity in the WEC and to unmodelled effects including quadratic viscous damping are established. The advantages of each method are compared, and excellent quality estimation results are obtained using both methods. Both methods are verified for use with advanced control strategies to improve power capture in WECs. Highlights: Wave excitation force is unmeasurable in reality but required for active control strategies. 1:25th scale experimental submerged multi-DOF WEC is used. Two Kalman filter approaches to wave force estimation are tested: a stochastic and a periodic method. Both methods perform well and can be implemented in real time using only measurable quantities.